Differential Inhibition of Equilibrative Nucleoside Transporter 1 (ENT1) Activity by Tyrosine Kinase Inhibitors - Jouan, Elodie (Eur J Drug Metab Pharmacokinet, 2021)
BACKGROUND AND OBJECTIVES: Equilibrative nucleoside transporter (ENT) 1 is a widely-expressed drug transporter, handling nucleoside analogues as well as endogenous nucleosides. ENT1 has been postulated to be inhibited by some marketed tyrosine kinase inhibitors (TKIs). To obtain insights into this point, the interactions of 24 TKIs with ENT1 activity have been analyzed. METHODS: Inhibition of ENT1 activity was investigated in vitro through quantifying the decrease of [(3)H]-uridine uptake caused by TKIs in HAP1 ENT2-knockout cells, exhibiting selective ENT1 expression. TKI effects towards ENT1-mediated transport were additionally characterized in terms of their in vivo relevance and of their relationship to TKI molecular descriptors. Putative transport of the TKI lorlatinib by ENT1/ENT2 was analyzed by LC-MS/MS. RESULTS: Of 24 TKIs, 12 of them, each used at 10 µM, were found to behave as moderate or strong inhibitors of ENT1, i.e., they decreased ENT1 activity by at least 35%. This inhibition was concentration-dependent for at least the strongest ones (IC(50) less than 10 µM) and was correlated with some molecular descriptors, especially with atom-type E-state indices. Lorlatinib was notably a potent in vitro inhibitor of ENT1/ENT2 (IC(50) values around 1.0–2.5 µM) and was predicted to inhibit these nucleoside transporters at relevant clinical concentrations, without, however, being a substrate for them. CONCLUSION: Our data unambiguously add ENT1 to the list of drug transporters inhibited by TKIs, especially by lorlatinib. This point likely merits attention in terms of possible drug–drug interactions, notably for nucleoside analogues, whose ENT1-mediated uptake into their target cells may be hampered by co-administrated TKIs such as lorlatinib.